Exploring Factors Associated with Diabetic Retinopathy Treatment Compliance Behaviour in Cape Town, South Africa - Annalie Wentzel (MDPI AG, 2021)
Complete patient adherence to treatment for diabetic retinopathy (DR) is critical to limit vision loss. There is a dearth of evidence regarding the reasons why South African patients referred for suspected vision-threatening DR stay compliant to or default their treatment. The current study sought to explore factors associated with treatment compliance among patients living with diabetes who have been referred for suspected vision-threatening DR in the Northern/Tygerberg sub-Structure (NTSS) public health care system of Cape Town, South Africa. A qualitative research approach was used where semi-structured in-depth interviews were conducted with 13 adult patients living with DR, and 2 key informants who are primary eye care providers. Thematic data analysis was conducted using taguette.org. Fear of going blind was the most notable patient-related factor associated with compliance. Notable patient-related barriers reported were forgetfulness and a poor state of health. Notable institution-related barriers included suboptimal information received from health care service providers, poor referral management by the organisation delivering retinal screening services, as well as the inaccessibility of the main NTSS hospital via telephone calls. All these factors were confirmed by the key informants of the current study. Finally, all patients and key informants agreed that SARS-CoV-2 negatively affected patients’ adherence to their DR treatment. Hence, scaling up of health care, referral, and appointment setting services could increase the uptake of treatment and retinal screenings among patients attending the Cape Town, NTSS public health care system.